PENGARUH KEBERADAAN PERUSAHAAN TERHADAP KONDISI SOSIAL EKONOMI MASYARKAT DESA PANGKE BARAT KABUPATEN KARIMUN - Muhammad Faritz; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Social mobility is the movement from a social class to another social class consisting of vertical mobility and horizontal mobility. The character of an open stratification system gave members of the community the opportunity to move or livelihood position as happened in the community of Desa Pangke Barat , Karimun regency that switches to livelihoods from fishermen or farmers to private empolyees. This research aims to analyze as well as researching the transition of livelihoods of people who originally worked as fishermen or farmers into private company employees in Desa Pangke Barat, Karimun regency. This research uses the method of observation, questionnaires and documentation with quantitative analysis described descriptively and the theory used is the theory of social change. The results of the analysis that has been done in this research indicate that the entry of industry in Desa Pangke Barat greatly influential on the development of the region itself, starting from the aspect of development, economy, education and even culture. One of the impacts of the industry in the middle of Desa Pangke Barat was the change in livelihood where there was a shift of orientation from agriculture sector to industrial sector and entrepreneurship. This industrialization process brought drastic changes to the people who live in Desa Pangke Barat, Karimun regency. As the livelihoods of those who originally lived by farming or as fishermen have now turned into laborers at the company in the local village. After the establishment of the company in Desa Pangke Barat there was a livelihood transition this is caused by people who see the existence of business opportunities. The alteration of the profession does not happen suddenly, surely the transfer of profession occurs because of problems in the old profession before. In this research people saw the opportunity after the establishment of the company in the Desa Pangke Barat so, make them did over the profession of this matter certainly have an impact on their lives as the income of respondents that was increased.Key word: Social, Changes, Jobs, Social Economy